Carbon Nanorings: 3D Bridged Carbon Nanoring/Graphene Hybrid Paper as a High‐Performance Lateral Heat Spreader (Small 46/2015). Issue 46 (7th December 2015) - Zhang, Jianwei; Shi, Gang; Jiang, Cai; Ju, Su; Jiang, Dazhi
Abstract : On page 6197, D. Jiang and co‐workers introduce a 3D bridged carbon nanoring (CNR)/graphene hybrid paper and a graphene paper without interlayer bridges. Due to the CNRs bridging the graphene sheets, the thermal transport ability in the normal direction of the hybrid paper is highly improved, which can be seen in the cover image as demonstrated by different colours. This also makes the hybrid paper an excellent lateral heat spreader. The growth of CNRs is achieved by the intercalation of polymer carbon sources and a metal catalyst in the confined space between graphene sheets.